Two Flavan Derivatives Isolated from Artocarpus dadah Grown in Lampung, Indonesia - Suhartati, Tati; Yandri; F. Suwandi, Jhons; Hadi, Sutopo (Asian Journal of Chemistry, 2012)
From the root bark of Artocarpus dadah grown in Lampung, Indonesia have successfully been isolated two flavan derivatives, afzelecin-3-O-a-L-ramnoside and chatecin. The structure of both compounds were determined based on physical properties and UV-VIS, IR and NMR spectroscopies.